2020
DOI: 10.3390/insects11100657
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Reproduction and Mass-Rearing of Sclerodermus brevicornis (Hymenoptera: Bethylidae), a Natural Enemy of Exotic Flat-Faced Longhorn Beetles (Coleoptera: Cerambycidae: Lamiinae)

Abstract: Many species of long-horned beetles are invasive pests causing significant economic damage in agro-forestry systems. They spend the majority of their life-cycle concealed inside natural wood or wooden packaging materials and are largely protected from adverse environmental conditions and pesticide sprays. Biological control via parasitoid natural enemies including members of the bethylid genus Sclerodermus, has proven effective against some long-horned beetles that are invasive in China. In Europe, the biocont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 79 publications
(112 reference statements)
1
9
0
Order By: Relevance
“…However, if one foundress could control the sex allocation of the other, we would expect that the ESS for the dominant foundress would be to produce only as many sons as could inseminate all female offspring maturing within the group and to allow the subordinate foundress to produce female offspring only. If sex allocation dominance were substantial, we would expect sex ratios to be very strongly female biased, irrespective of foundress number (as observed in this study and previously by Hong et al, 2008; Li et al, 2010; Li & Sun, 2011; Tang et al, 2014; Lupi et al, 2017; Wang et al, 2016; Wei et al, 2017; Yang et al, 2018; Abdi et al, 2020a; Jucker et al, 2020; Zhao et al, 2020). We would also expect that, due to limited mating capacity of adult males, the numbers of males in broods would increase gradually as brood sizes increase (as observed in this study and previously by Kapranas et al, 2016; Abdi et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, if one foundress could control the sex allocation of the other, we would expect that the ESS for the dominant foundress would be to produce only as many sons as could inseminate all female offspring maturing within the group and to allow the subordinate foundress to produce female offspring only. If sex allocation dominance were substantial, we would expect sex ratios to be very strongly female biased, irrespective of foundress number (as observed in this study and previously by Hong et al, 2008; Li et al, 2010; Li & Sun, 2011; Tang et al, 2014; Lupi et al, 2017; Wang et al, 2016; Wei et al, 2017; Yang et al, 2018; Abdi et al, 2020a; Jucker et al, 2020; Zhao et al, 2020). We would also expect that, due to limited mating capacity of adult males, the numbers of males in broods would increase gradually as brood sizes increase (as observed in this study and previously by Kapranas et al, 2016; Abdi et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…Females were then stored in a refrigerator (5 ± 0.5°C) to synchronise parasitoid and host availability on emergence and were around two weeks old when used in experiments. Previous studies have shown that such storage does not greatly affect their subsequent performance (Jucker et al, 2020). Cultures were maintained in a climate chamber at 25 ± 1°C, a 16 L:8D diurnal cycle and a relative humidity of 60 ± 5%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2020a,b,c; Jucker et al. 2020). These cases therefore suggest that we need to identify additional factors that can favor female‐biased sex ratios.…”
Section: Figurementioning
confidence: 99%
“…Evans 1962). Yet, studies of behaviour and also their biology at large are mostly restricted to species of agricultural importance, as their immatures parasitise some crop and storage pests (Kühne and Becker 1974;Gordh and Hawkins 1981;Gordh 1998;Cheng et al 2004;Gao et al 2016;Jucker et al 2020).…”
Section: Flat Wasps and Their Parasitoid Immaturesmentioning
confidence: 99%